Utilization of Liquid Smoke from Siwalan Fruit Skin Waste as an Organic Pesticide Against Armyworm Mortality - Septiyanna Rokhmawati Dewi; Dyah Ratri Nurmaningsih; Arqowi Pribadi (Fakultas Teknik, 2022)
Pest attacks that result in reduced crop yields require alternative control that is able to prevent damage to agricultural land. Organic pesticides are environmentally friendly pesticides because the materials used are derived from natural ingredients, one of which is liquid smoke, namely liquid smoke made from natural ingredients containing cellulose, hemicellulose, and lignin. This study was to determine the effect of giving liquid smoke of siwalan peel waste as an organic pesticide. Liquid smoke is obtained from the combustion process with a little oxygen at a certain temperature. The content of compounds in liquid smoke was analyzed using GCMS. Pyrolysis results obtained dark brown liquid smoke, clear, has a smoke-like odor (sangit), and has a watery texture which is used as an organic pesticide on spodoptera litura with varying concentrations of 5%, 7%, 9%, 11%, and 13%. The results of the GCMS analysis found 18 components of the liquid smoke of siwalan rind waste, among the compounds that function as organic pesticides are phenol, furfuran, acetone, and palimitic acid. The results of the analysis of the mortality of spodoptera litura sequentially showed the average value of mortality in 2 repetitions, namely 5%, 10%, 15%, 20%, and 35%. The greater the concentration of liquid smoke, the higher the mortality value. However, it is less effective to kill spodoptera litura quickly, even mortality at a maximum concentration of only 35% or has not reached the death rate of 50% of test animals.